Muhammad Hamdi Yazır’s Contributions to Islamic Education in Modern Türkiye: A Cultural Anthropology Perspective - Titis Thoriquttyas; Ahsin; Khasbulloh (Al'Adalah, 2024)
The transition from the Ottoman Empire to the secular Republic of Turkey significantly impacted Islamic education, as madrasahs were closed and a secular education system was adopted. This study analyzes the intellectual contribution of Muhammad Hamdi Yazır, who played a pivotal role in reconciling Islamic philosophy with modern secularism in moderating traditional Islamic education with the secularism orders through his work, Hak Dini Kur'an Dili. Yazır's approach integrated rational knowledge (ulum al-aqliyah) and religious knowledge (ulum al-naqliyah) to maintain Islamic teachings within the secular framework. This study uses the lens of cultural anthropology to analyze Yazır's contribution as mentifacts (intellectual heritage), sociofacts (social structures), and artifacts (educational materials). Unlike previous studies that focused more on theological and philosophical aspects, this study reveals how Yazır's ideas are not only in the form of ideas but are also influenced by social structures and manifested in educational materials. The analysis demonstrates how Yazır's intellectual efforts adapt Islamic education to modernity without negating its essence, ensuring its relevance in contemporary Turkish society. This study provides new insights into the transformation and sustainability of Islamic values ​​in the secular education system and recommends further comparative studies to explore similar dynamics in other Islamic contexts.